FATTY ACID COMPOSITION AND TOTAL LIPID CONTENT IN PROTEIN HYDROLYSATES OF SHRIMP HEADS - JAIME LÓPEZ-CERVANTES; DALIA I. SÁNCHEZ-MACHADO; CAROLINA BUENO-SOLANO; OLGA N. CAMPAS-BAYPOLI; NORMA P. ADAN-BANTE (International Journal of Pharma and Bio Sciences, 2013)
Lipids, being recognized as an important source of energy, are major constituents of our diets. The by-products of the shrimp industry have high added value, one of these is protein hydrolyzate obtained by lactic fermentation. In this research concerning fermented shrimp heads, three consistencies of hydrolyzed protein were analyzed: liquid, paste, and powder. The lipid content was in a range of 4.33-7.75% for the hydrolyzed liquid, 6.32-9.51 % for the concentrate in paste form and 24.28-36.78% for the hydrolyzate as a powder. Gas chromatography was employed in the determination of the fatty acid composition (%). The fatty acid in highest concentration in the liquid hydrolyzate was eicosapentanoeic acid (C20:5n3), while the paste and the powder hydrolyzate registered was hexadecanoic acid (C16:00). The paste and the powder hydrolyzates, contained a higher concentration saturated fatty acid than unsaturated. This research complements the characterization of the protein hydrolyzate obtained from the fermentation of shrimp heads.